Democratic Electoral Systems around the world, 1946–2020. (August 2022) - Bormann, Nils-Christian; Golder, Matt
Abstract: This research note describes an update to Bormann and Golder's 2013 Democratic Electoral Systems (DES) dataset. We extend the temporal scope of the previous dataset by adding information for all legislative and presidential elections that took place in democratic states from 2011 through 2020. More significantly, the DES dataset now includes information on all elections that are considered democratic by at least one of five different measures of regime type: Democracy and Dictatorship (DD), Freedom House (FH), Polity5, Boix-Miller-Rosato (BMR), and Varieties of Democracy (V-Dem). The result is that the new DES dataset has greater utility and is over 30% larger than the previous one. A brief overview of the data is presented.